2021
DOI: 10.3389/fnbot.2020.617293
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Inequalities Based Robust Model Predictive Control for Vehicle Considering Model Uncertainties, External Disturbances, and Time-Varying Delay

Abstract: In this paper, we design a robust model predictive control (MPC) controller for vehicle subjected to bounded model uncertainties, norm-bounded external disturbances and bounded time-varying delay. A Lyapunov-Razumikhin function (LRF) is adopted to ensure that the vehicle system state enters in a robust positively invariant (RPI) set under the control law. A quadratic cost function is selected as the stage cost function, which yields the upper bound of the infinite horizon cost function. A Lyapunov-Krasovskii f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…then, the MPC problem can be converted to the standard multi-parameter quadratic programming form of equation (9), where…”
Section: Design Of Empc Controllermentioning
confidence: 99%
See 3 more Smart Citations
“…then, the MPC problem can be converted to the standard multi-parameter quadratic programming form of equation (9), where…”
Section: Design Of Empc Controllermentioning
confidence: 99%
“…Thus the Theorem 1 is proved. Note3: Since the MPC control problem in (7)(8) is not a standard mpQP problem, and due to the particularity of turboshaft engine-rotor system, the influence of disturbance input (rotor system input) on the derivation process has to be considered in the conversion of problem (7) (8) to problem (9). Therefore, we need to first convert the MPC problem of turboshaft engine-rotor system into a standard mpQP problem, which is the main role of Theorem 1.…”
Section: Design Of Empc Controllermentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al designed a robust model predictive control (RMPC) controller for vehicles subjected to bounded model uncertainties, norm-bounded external disturbances and bounded timevarying delay. Simulation results showed that the proposed vehicle dynamic controller can steer vehicle states into a very small region near the reference tracking signal even in the presence of external disturbances, model uncertainties and time-varying delay [17]. Samuel et al used model predictive control and proportional integral derivative control for lane keeping maneuvers of an autonomous vehicle.…”
Section: Introductionmentioning
confidence: 99%